Deltagelsens æstetik – om at tale, lytte og adlyde - Breinbjerg, Morten; Fritsch, Jonas (K&K - Kultur og Klasse, 2014)
In this article we discuss aesthetics of participation as a sensory, affective and reflective engagement with the world and the historical, physical, material, political and cultural relations that form our world. We develop a theoretical understanding building on the work of Michel Serres and Jacques Rancière to unfold participation as continuous fluctuations between individual/collective, signal/noise, order/chaos in a distribution of the sensible, following a politics of aesthetics. Through the analysis of two auditory, interactive installations – BUG and Ekkomaten – we show how the aesthetics of participation arises from- and modulates complex communicative and affective relations between individuals, collectives and places. Through their crafting and design, both BUG and Ekkomaten effect a transformation of the distributions of the sensible through digital sonifications, giving its users the possibility to redefine their relational engagement with issues of surveillance in the former DDR (BUG) and the community of the residential area Møllevangen in Aarhus, Denmark (Ekkomaten). Following this, we discuss how future (participatory) design projects can benefit from cultivating an aesthetics participation where aesthetics describes the relation between forms of experience, the distribution of the sensible and the potential for participation.